Effectiveness of Umroh Budget Funds on the Increasing Number of Umroh Pilgrimages at PT Hanan Nusantara Tabung Haji Umroh - Amalia Aisyah Putri; R. Yuniardi Rusdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine effectiveness bailout system to improve​ the number of umrah pilgrims at PT Hanan Nusantara – Tabung Haji Umrah. This research uses the method study qualitative descriptive method and data collection process carried out employing field research (direct research in the field). The determination of the sample to be used in this study is the Branch Head, Umrah pilgrims of PT. Hanan Nusantara - Tabung Haji Umroh and SPV manifest (who regulates the entire Umrah trip). Findings This research shows indicator effectiveness used​ as a reference in measuring the extent to what extent this program has succeeded in improving a number of worshipers in each month.